Metaplastic breast cancer: A review. (February 2023) - Thomas, Horatio R.; Hu, Bonnie; Boyraz, Baris; Johnson, Andrew; Bossuyt, Veerle I.; Spring, Laura; Jimenez, Rachel B.
Abstract: Metaplastic breast cancer (MpBC) is an uncommon aggressive malignancy that is associated with a poor prognosis. Due to its rarity, the relationships between the clinical and pathological features of MpBC, treatment approach, and clinical outcomes remain underexplored. In the following review article, we synthesize the existing data on the clinical, pathological and genomic features, management, and outcomes of MpBC. We also identify potential targets for future clinical trials. Graphical Abstract: ga1 Highlights: Metaplastic Breast Cancer consists of epithelial and sarcoma-like mesenchymal cells. It manifests as a large mass and usually metastasizes without nodal involvement. Aberrant AKT and cadherin expression confer chemoresistance and metastatic potential. Surgical resection and radiation therapy improves local control and survival. Effective systemic agents for definitive and salvage therapy remain ill-defined.